Firing up the Anthropocene: Conflagration, Representation and Temporality in Modern Australia - Hayward, Philip (Text Matters: A Journal of Literature, Theory and Culture, 2022)
The European colonization of Australia introduced a new population into a continent in which Indigenous people had practiced cyclic burning as a form of ecosystem maintenance since time immemorial. The settlers’ complete disdain for Indigenous knowledge and related practices caused these customs to largely fall into disuse. One result of this was an increased vulnerability of landscapes to bush fires, a factor that has risen to the fore in the early twenty-first century. The fires that have swept across the landscape with increasing frequency and ferocity have provoked fears of a rolling, fiery apocalypse that might make living in many areas of the continent untenable. This marks a new phase of settler anxiety that has been fuelled by extensive coverage of fires on broadcast and digital media platforms. Blending discussions of Indigenous culture, 19th-21st-century European settler visual art, literature and modern communications media, this article begins by examining the nature of Anthropocene modernity and the very different worldviews and practices of Australian Indigenous peoples. Particular attention is given to senses of time and of living and working with fire. Subsequent sections open up the topic with regard to the planetary present and how we might adjust to the future.